(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
Over time, businesses have added additional components, such corporate governance, service-dominant thinking, and sustainable business. Examples of these include corporate social responsibility. It used to be said that an organization’s main responsibility was to maximize profits for its stakeholders at the expense of its ability to improve society as a whole. Ecology, another important component that was previously disregarded, is now receiving the attention it deserves. A “business case” for corporate sustainability is a concept that more and more businesses, environmental groups, and others are adopting to bolster their sustainable business practises. No company can stay in business for very long if it withdraws from these operations. Therefore, it is now essential to engage in responsible corporate citizenship in the contemporary economic environment by Understanding these phrases and integrating them into company social culture is increasingly essential. The theoretical examination of corporate social responsibility (CSR) in this article will primarily center on the triple bottom line (TBL) in terms of the economic, social, and environmental components. The study of corporate social responsibility (CSR) for sustainable business will be built around the triple bottom line, with a focus on the importance of this concept for running sustainable businesses. The value that companies may provide to their clientele will determine how corporate businesses turn out.